PENDIDIKAN ISLAM MENCETAK MANUSIA RAHMATAN LIL ‘ALAMIN - Hj Farihatun (STKIP Paris Barantai, 2011)
Philosophy education theory and have to consider the context with supra system, context with importance of requirement of human and society, context with nation and state, context with cultural social, context with change in going to the society madani Indonesia. Formulate the mission and vision education of Islam clearlyly and precisely. Formulation of education mission determine the direction, stages;steps and map of journey to realize the vision and have to expressed in the form of formal statement concerning especial purpose to be realized. Formula vision in the form of abysmal mind of reality now, mean something that wish to be created, something that will be realized have to expressed in the form of clear sentence, positive, realistic, oppose, invitor partipasi and clearlyly show the assumption concerning the future picture wishing to be realized the based on values ilahiyah. Formulation of mission and vision education of Islam, is not locked out of the human duty as khalifah fil ardi for the agenda of developing life of prosperous world, democracy, fair, dynamic, harmonious, make everlasting, meekly law, is based on values ilahiyah in society madani Indonesia. owning the identity pursuant to Islam values and Indonesia culture.Â Kata Kunci: Pendidikan Islam, Manusia, Rahmatan Lil â€™alamin